Oral microbial changes, oral mucositis and febrile neutropenia during myelosuppressive chemotherapy in patients diagnosed with a solid tumor or lymphoma - Zecha, Judith A. E. M.; Raber-Durlacher, Judith E.; Brandt, Bernd W.; Buijs, Mark J.; Zaura, Egija; de Lange, Jan; Smeele, Ludwig E.; Laheij, Alexa M. G. A. (Frontiers in Oral Health, 2024)
ObjectivesTo evaluate the possible changes of the oral microbiome during myelosuppressive chemotherapy (CT) and to investigate the potential relationship between the oral microbiome, the presence of oral mucositis (OM) and febrile neutropenia (FN).MethodsA prospective, longitudinal, observational study was conducted in patients receiving myelosuppressive CT for a solid tumor or lymphoma. Oral rinsing samples were retrieved before, during and after the start of CT, but also when OM or FN was present. The samples were analyzed using 16S rRNA gene amplicon sequencing and statistical analysis was performed using alpha (Shannon) and beta (PERMANOVA) diversity analyses. Furthermore, differential abundances were analyzed using ALDEx2v1.32.0. Differences between groups were calculated using the Mann Whitney U-test, Kruskal-Wallis test and Wilcoxon Signed Rank using R.ResultsForty-six patients, with a mean follow up of 114 days, were included for analysis and a total of 138 oral rinsing samples were available in the CLR-transformed data for PERMANOVA and 137 samples—for alpha diversity calculation. Significant changes in alpha diversity were seen when OM or FN was present. Moreover, significant changes were seen in beta diversity during the course of the CT treatment and when OM was present. Genera showing substantial changes in relative abundance were Streptococcus during the course of CT treatment and Prevotella, Fusobacterium, Selenomonas, Actinomyces and Leptotrichia when OM was present.ConclusionChanges in the oral microbiome were observed during the CT-regimen and when OM was present. Furthermore, changes of the oral microbiota during FN episodes were observed; however, larger studies should be performed to substantiate our results.